Short-Term Molecular Acclimation Processes of Legume Nodules to Increased External Oxygen Concentration - Avenhaus, Ulrike; Cabeza, Ricardo A.; Liese, Rebecca; Lingner, Annika; Dittert, Klaus; Salinas-Riester, Gabriela; Pommerenke, Claudia; Schulze, Joachim (Frontiers in Plant Science, 2016)
Nitrogenase is an oxygen labile enzyme. Microaerobic conditions within the infected zone of nodules are maintained primarily by an oxygen diffusion barrier located in the nodule cortex. Flexibility of the oxygen diffusion barrier is important for the acclimation processes of nodules in response to changes in external oxygen concentration. The hypothesis of the present study was that there are additional molecular mechanisms involved. Nodule activity of Medicago truncatula plants were continuously monitored during a change from 21 to 25 or 30 % oxygen around root nodules by measuring nodule H2 evolution. Within about two minutes of the increase in oxygen concentration, a steep decline in nitrogenase activity occurred. A quick recovery commenced about eight minutes later. A qPCR-based analysis of the expression of genes for nitrogenase components showed a tendency towards upregulation during the recovery. The recovery resulted in a new constant activity after about 30 minutes, corresponding to approximately 90 % of the pre-treatment level. An RNAseq-based comparative transcriptome profiling of nodules at that point in time revealed that genes for nodule-specific cysteine-rich (NCR) peptides, defensins, leghaemoglobin and chalcone and stilbene synthase were significantly upregulated when considered as a gene family. A gene for a nicotianamine synthase-like protein (Medtr1g084050) showed a strong increase in count number. The gene appears to be of importance for nodule functioning, as evidenced by its consistently high expression in nodules and a strong reaction to various environmental cues that influence nodule activity. A Tnt1-mutant that carries an insert in the coding sequence (cds) of that gene showed reduced nitrogen fixation and less efficient acclimation to an increased external oxygen concentration. It was concluded that sudden increases in oxygen concentration around nodules destroy nitrogenase, which is quickly counteracted by an increased neoformation of the enzyme. This reaction might be induced by increased formation of NCR peptides and necessitates an efficient iron supply to the bacteroid, which is probably mediated by nicotianamine.